Estilos de crianza y niveles de autoestima en los estudiantes de educación media de una institución educativa en Mahates Bolívar - Arzuza Barrios, Ana Milena; Martínez González, Yojaira (Universidad Antonio Nariño, 2023)
Children and adolescents have their families as a referent or a model to follow, therefore the way they are treated by can influence in their behavior and in the way how they face situations in life. The main purpose of this investigation was to stablish the relationship between parenting styles and students'self-steem from an educational institution located in Mahates - Bolivar. An empiric-analytical approach was used, with a descriptive and correlational design, with a non-experimental methodology. 38 students between15 and 17 years old from this Institution are the sample we used. The type of sampling was non-probabilistic for convenience, the data collection techniques used was L. Steinberg the parenting styles scale and Stanley Coopersmith self esteem inventory. Once the data has been obtained and processed, we can highlight the finding of a relationship moderate and strong existing between the parenting styles compromise subscale home self esteem with a correlation coefficient 0.607.